1998
DOI: 10.1021/jf971096s
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and Flocculation of High-Pressure-Treated β-Lactoglobulin-Stabilized Emulsions:  Comparison with Thermal Treatment

Abstract: High-pressure treatment (HPT) has been shown to induce significant levels of flocculation in model oil-in-water emulsions stabilized by β-lactoglobulin at neutral pH, as indicated by changes in droplet size distribution and rheological behavior. Light microscopy has also provided additional evidence of extensive droplet flocculation following severe treatment. The proportion of unadsorbed protein greatly influences the extent of flocculation, and this may explain in part the nature of these pressure-induced ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 24 publications
0
23
3
Order By: Relevance
“…Liquidlike emulsions can be converted into solid-like emulsion gels on heating [111]. Static high-pressure treatment of ␤-lactoglobulin in emulsions can also have a significant influence on protein aggregation and emulsion stability [112][113][114].…”
Section: 4ˇ-lactoglobulinmentioning
confidence: 99%
“…Liquidlike emulsions can be converted into solid-like emulsion gels on heating [111]. Static high-pressure treatment of ␤-lactoglobulin in emulsions can also have a significant influence on protein aggregation and emulsion stability [112][113][114].…”
Section: 4ˇ-lactoglobulinmentioning
confidence: 99%
“…On the other hand, Dickinson and James (1998) have studied the HP effect on emulsions stabilized with b-lactoglobulin. They observed an increase in flocculation with HP treatment, especially at high non-adsorbed protein concentrations.…”
Section: Article In Pressmentioning
confidence: 99%
“…HP technology can both preserve foods and modify functional properties of food components (Dickinson & James, 1998;Montero, Ferna´ndez-Dı´az, & Go´mez-Guille´n, 2002). It is well known that pressure has a disruptive effect on the tertiary and quaternary structure of most globular proteins (Puppo et al, 2004;Tedford, Smith, & Schaschke, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Examination of the overall droplet size distributions for the high- pressure-treated emulsions suggests that treatment induces extensive droplet¯occulation. It is interesting to note that previous studies carried out on b-Lg emulsions have also shown¯occulation, 43 although the effect of high pressure on d 43 and creaming behaviour was somewhat less when the treatment was applied after emulsion formation. 14 On the basis of the experimental results presented in this paper and data from previous studies 10,20,22 we assume that high-pressure processing leads to the dissociation of the electrostatic protein±polysacchar-ide complex(es).…”
Section: Effects Of Ionic Strength and Phmentioning
confidence: 94%